Assessment of combined exposure to intermediate-frequency electromagnetic fields and pulsed electromagnetic fields among library workers in Japan - Yamaguchi-Sekino, Sachiko; Taki, Masao; Ikuyo, Miwa; Esaki, Kaoru; Aimoto, Atsuko; Wake, Kanako; Kojimahara, Noriko (Frontiers in Public Health, 2022)
Objective: To assess the exposure levels of electromagnetic fields (EMFs) among library workers in Japan, especially focusing on the co-exposure to intermediate-frequency EMF (IF-EMF) and pulsed EMF, as a proposal for a new methodology for epidemiological research. Methods: The exposure sources were an electromagnetic type-electronic article surveillance (EM-EAS, IF-EMF) gate and activator/deactivator of the anti-theft tags we named as a “book check unit” (BCU, pulsed EMF). Short-term exposures were: E1) whole body exposure from the EAS gate when sitting within 3 m, E2) local exposure to transient IF-EMF during passing through or beside the EAS gate, and E3) local exposure to pulsed magnetic field on use of BCU. We used 549 completed questionnaires to obtain exposure parameters and working conditions. E1-E3 were evaluated based on the exposure level relative to reference level (RL; E1) or basic restrictions (BR; E2 and E3) of the International Commission on Non-Ionizing Radiation Protection (ICNIRP) 2010 guidelines. The cumulative long-term exposure (D1) or repeated transient exposure (D2, D3) which led by E1-E3 and working conditions collected in questionnaire survey, were also defined to assess the exposure assuming actual working conditions. Four exposure patterns were defined according to various exposure scenarios. Results: The ICNIRP guideline levels were not exceeded in any of the cases in E1-E3. The median of the D1 was 1.24 and more than 85% of respondents’ values were below 10, while the maximum value was 512.6, indicating that cumulative long-term exposures were low in most cases. The same tendency was observed in repeated transient exposure from the EM-EAS gates (the median of D2 was 5.42). However, there were several cases in which D1 and D2 were more than 10 times the median. The median of D3 was 10.5, and most respondents' D3 were greater than D2 although the results depended on the assumptions made for the estimation. Conclusion: The present study conducted the assessment of the combined exposure to IF-EMF and pulsed EMF among library workers in Japan by evaluating both short-term exposures (E1-E3) and long-term exposures (D1-D3) for assumption of actual working conditions. These results provide useful information for future epidemiological studies.